Entertainment Industry as a Public Sphere: Interactional Sociolinguistic Analysis of Pakistani Drama and a YouTube Podcast Comment Sections (PAKISTAN JOURNAL OF LAW, ANALYSIS AND WISDOM, 2024)
This study is a comparative analysis of two entertainment avenue/ genres: TV drama and YouTube podcast shows, as an adequate public sphere. The proposed hypothesis that there is a stark contrast between the audience of these two genres, is rationalized through the theory of mass communication by McQuail (2010), the analytical framework of exchange structure (Sinclar and Coulthard, 2013), Habermas’ theory of public sphere and Stenstrom’s (1996) taxonomy of primary acts. The detailed study based on interactional sociolinguistic analysis reveals that TV drama audiences are numbed towards social and cultural malice because the said platform itself does not problematize or generate a critical discourse about them. Hence, its audience’s comment analysis supports their reciprocal behavior. On the contrary, the podcast audience seem to be astute, attentive, and intelligent which is again concluded based on their comments. Its audience responds to the essential discussion of societal problems that the host addresses. This study therefore suggests that internet podcasts are a better public sphere and a platform for the betterment of a community, rather than TV dramas that serve no educational purpose but only further the internalized stigmas.